Temporal bone Manifestations of Eosinophilic Granuloma - Acharya, B. K. (Springer India, 2001)
Eosinophilic granuloma is one of the triad of conditions collectively known as Histiocytosis-X. It is an uncommon granulomatous diseas which can affect the temporal bone(1) Allthough initially quiescent the disease may erode the mastoid cortex, destroy tegmen and extend into the cranial as well as erode the semicircular canals, cochlea or facial canal, giving rise to facial palsy. These lesions almost always become infected and can confused with chronic otomastoiditis. When diagnosed, theraphy consists of conservative surgery, radiation theraphy, steroids and chemotherapy(2).